A higher degree of polyethylene irradiation is associated with a reduced risk of revision for aseptic loosening in total hip arthroplasties using cemented acetabular components: an analysis of 290,770 cases from the National Joint Registry of England, Wales, Northern Island and the Isle of Man - Davis, Edward T. (Bone Joint Res, 2020)
AIMS: To investigate the effect of polyethylene manufacturing characteristics and irradiation dose on the survival of cemented and reverse hybrid total hip arthroplasties (THAs). METHODS: In this registry study, data from the National Joint Registry of England, Wales, Northern Ireland and the Isle of Man (NJR) were linked with manufacturing data supplied by manufacturers. The primary endpoint was revision of any component. Cox proportional hazard regression was a primary analytic approach adjusting for competing risk of death, patient characteristics, head composition, and stem fixation. RESULTS: A total of 290,770 primary THAs were successfully linked with manufacturing characteristics. Overall 4,708 revisions were analyzed, 1,260 of which were due to aseptic loosening. Total radiation dose was identified as a risk factor and included in the Cox model. For statistical modelling of aseptic loosening, THAs were grouped into three categories: G1 (no radiation); G2 ( > 0 to < 5 Mrad); and G3 ( ≥ 5 Mrad). G1 had the worst survivorship. The Cox regression hazard ratio for revision due to aseptic loosening for G2 was 0.7 (95% confidence interval (CI) 0.58 to 0.83), and for G3 0.4 (95% CI 0.30 to 0.53). Male sex and uncemented stem fixation were associated with higher risk of revision and ceramic heads with lower risk. CONCLUSION: Polyethylene irradiation was associated with reduced risk of revision for aseptic loosening. Radiation doses of ≥ 5 Mrad were associated with a further reduction in risk. Cite this article: Bone Joint Res 2020;9(9):563–571.